Amplitude Scintillation Severity and Fading Profiles Under Alignment Between GPS Propagation Paths and Equatorial Plasma Bubbles - Sousasantos, J.; Affonso, B. J.; Moraes, A.; Rodrigues, F. S.; Abdu, M. A.; Salles, L. A.; Vani, B. C. (Space Weather, 2022)
Ionospheric scintillation and fading events over low‐latitude regions are often caused by severely depleted geomagnetic field‐aligned structures known as Equatorial Plasma Bubbles. These events are subject of interest to scientific investigations and concern to technological applications. Over the past several years, most of scintillation studies have focused on the dependence of these events on density gradients, location, local time, geomagnetic conditions, and so forth. This work presents a discussion about the role of the alignment between the signal propagation path and the depleted structures or, equivalently, the geomagnetic field lines, on the observed scintillation and deep fading characteristics. Data from three stations (dip latitudes: 16.13°S, 19.87°S, and 22.05°S) located around the Equatorial Ionization Anomaly (EIA) region were used to assess the amplitude scintillation severity and the deep fading events features under aligned and nonaligned conditions. The results show that the alignment condition plays a crucial role in the occurrence of strong scintillation. The study also revealed that, as stations far from the crests of the EIA are considered, the alignment influence seems to increase, and that a combination of strong plasma density fluctuation and increased aligned path is, presumably, the configuration under which the most severe scintillation and drastic deep fading events are observed. The results indicate that this conjunction is typically met in regions somewhat distinct from that with largest plasma density background over the Brazilian region, therefore, strongest scintillation and largest deep fading rates were observed by a station slightly off‐the EIA peak. Plain Language Summary Several phenomena from space weather affect technological applications dependent on positioning systems relying on information from the Global Navigation Satellite System. Over low‐latitude regions the most prominent events are the Equatorial Plasma Bubbles. These plasma bubbles are depleted structures that may reach thousands of km and affect radio signals causing deep fading events and the so‐called ionospheric scintillation. Very often the studies regarding plasma bubbles and the ensuing ionospheric scintillation and deep fading events consider the plasma density deviation caused by the presence of these plasma bubbles over a region with enhanced background plasma density, as is the case of the Equatorial Ionization Anomaly, however, this work shows that other aspects must also be considered. In this work scintillation data from ground receivers deployed over the southern Brazilian region during a period of intense occurrence of scintillation were used to uncover new aspects responsible for severe scintillation and deep fading events. It was shown that the alignment between the transionospheric signals and the plasma bubbles is related to the severe scintillation and to the increase in the deep fading events rate. It was also found that the conjoint configuration of strong plasma density deviation and increased alignment is probably responsible for the more drastic events. Key Points Space weather impacts on Global Navigation Satellite System communication over low‐latitude regions Equatorial plasma bubbles field‐aligned nature and its influence on transionospheric signals aligned with these depleted plasma structures Ionospheric scintillation and deep fading characteristics according to the propagation path